열전도성 점착제 응용을 위한 고분자 기반 탄소나노소재 복합체 제조 및 특성 평가 - 이병주(Byeong-Joo Lee); 조성일(Sung-Il Jo); 윤은혜(Eun-Hye Yoon); 이애리(Ae-Ri Lee); 이우영(Woo-Young Lee); 허성규(Sung-Gyu Heo); 황재성(Jae-Sung Hwang); 정구환(Goo-Hwan Jeong) (Biuletyn Uniejowski, 2020)
A polymer-based carbon nanomaterial composite was fabricated and characterized for the application of a thermal conductive adhesive. Low-dimensional carbon nanomaterials with excellent thermal conductivity such as carbon nanotube (CNT) and graphene were selected as a filler in the composite. Thermal, electrical and adhesive properties of the composite were investigated with respect to the morphology and content of the low-dimensional carbon nanomaterials. As a result, the composite-based adhesive fabricated by the loading of surface-treated MWCNTs of 0.4 wt% showed uniform dispersion, moderate adhesion and effective heat dissipation properties. Finally, it was confirmed through the thermal image analysis of LED module that the temperature reduction of 10℃ was achieved using the fabricated composite adhesive with MWCNT-6A. Expecially, heat dissipation performance of the optimized composite adhesive was evident at the hot spot in the module compared to other samples mixed with graphene or different MWCNT loading ratios.